Collection and Conservation of Landraces of Perilla frutescens (Linn.) Britt from Northeastern Hill (NEH) Region of India - Singh, S K; Kole, P C; Misra, A K; Roy, Somnath (Indian Journal of Hill Farming, 2017)
Perilla is one of the underutilized oilseed crop of Northeastern hill (NEH) region of India. In this study a total of 28 Perilla accessions, collected from diverse agro-ecological areas of NEH region of India. The qualitative traits and oil yield were assessed. A wide range of variation was observed for traits; early plant vigour, plant shape, leaf colour, seed colour, seed size and oil yield. Accessions namely IC599246, IC599247, IC599233 and IC599258 were recorded more than 48% oil yield. On the basis of Hierachical clustering using Wards method all the accessions were clustered into two major clusters A and B. The utilization of the crop though limited but has got potentiality for cultivation in large scale. Utilization of this oilseed crop by the local tribal people has been discussed. The nutritive value of the crop is also documented.